Structure and antagonism of the receptor complex mediated by human TSLP in allergy and asthma - Kenneth Verstraete (Nature Portfolio, 2017)
The pro-inflammatory cytokine thymic stromal lymphopoietin (TSLP) is a promising therapeutic target. Here the authors characterize the assembly mechanism of the receptor complex driven by human TSLP, and its antagonism by the monoclonal antibody Tezepelumab and a fusion protein comprising the TSLP receptors.